Journey to the center of the common envelope evolution: Inner dynamics of the post-dynamical inspiral - Gagnier, Damien; Pejcha, Ondr̆ej (Astronomy and astrophysics, 2025)
Three-dimensional hydrodynamical simulations of common envelope evolution are often terminated soon after the initial dynamical plunge of the companion transitions into a long-lasting post-dynamical inspiral with a slowly varying semimajor axis, ab. This premature termination is often due to insuﬃcient numerical resolution and challenges associated with the softening of the gravitational potential of the two cores. In this work we used statically reﬁned 3D hydrodynamical simulations to study non-accreting binaries orbiting inside a common envelope, exploring the eﬀects of varying numerical resolution, δ, gravitational potential softening prescriptions, and the associated softening length scale, . We ﬁnd that quantities such as the binary inspiral timescale or the volume-averaged shearing rate typically converge to asymptotic values only for ≤ 0.1ab and δ ≤ 6 × 10−3ab, with smaller requiring correspondingly smaller δ. This suggests that many of the contemporary simulations could eﬀectively be under-resolved. After a few tens of binary orbits, the two cores become surrounded by a corotating, nearly hydrostatic gas structure that resembles the shared envelope of a contact binary. We propose that this structure is responsible for the slowing of the dynamical inspiral, leading to an asymptotic inspiral timescale of approximately 105 orbital periods for a binary mass ratio q = 1/3, and approximately 106 orbital periods for a binary mass ratio q = 1. Even in the absence of magnetic ﬁelds, we observe intermittent polar outﬂows collimated by partially centrifugally evacuated polar funnels. We discuss the implications for the long-term evolution in the post-dynamical inspiral phase and the ultimate emergence of the post-common-envelope binary.
Gesehen am 25.08.2025